Answer to ECG Quiz no. 32 - Millar, R Scott (SA Heart Journal, 2017)
Trifascicular block cannot be diagnosed from a single ECG showing bifascicular block with prolonged PR. The risk of AV block during anaesthesia and surgery is low. If AV block occurs, it is likely to be vagally induced (Wenckebach), rather than Mobitz II. The risk of a temporary pacemaker is not usually justified.